More Internet for More Employment and Earnings: A Causal Estimation for Costa Rica - Efraín Boza-Nú\~nez; Luis Vargas-Montoya; Juan Robalino (International Telecommunications Society (ITS), 2023)
Information and communications Technologies (ICT) are crucial in people's daily activities, including the job-related ones. Previous literature has acknowledged the potential of ICT to enhance labor market outcomes. However, empirical evidence is scarce and concentrated in developed countries. By using a rich longitudinal dataset, we apply a novel Differences and Differences (DiD) method to estimate the effect of the access to computers and internet over the labor market participation, employment and earnings. We further test whether there are complementarity effects of having access to the internet and computers simultaneously on the labor market outcomes and the likely differential effect by having access to broadband instead of lower speed connections. We found that the access to computers and the internet positively affects labor market participation, employment and earning. We further found that the simultaneous access to the internet and computers enhances their effect on employment and earnings. Policy makers should be aware that, in the digital era, the access to ICT is crucial to enhance the labor market outcomes. Particularly for developing countries, which along with poorer labor markets outcomes face higher digital divides.
Keywords: 330